Exosomal Dvl3 promoted the aggressive phenotypic transformation of RA-FLS via wnt pathway - Weixing Tan; Ning Chen; Yang Qiu; Xiaomei Feng; Shuwen Li; Yongjin Zhang; Haoran Li; Jie Gao; Dongbao Zhao (Taylor & Francis Group, 2022)
Objective This study was performed to explore the function and mechanism of Dvl3 in RA-FLS by exosome intervention. Methods The expression pattern of Dvl3 was examined by IHC, WB, and qPCR. Modified exosomes obtained from culturing supernatant of RA-FLS infected with Dvl3 over expression (OE) lentivirus were administrated to the target RA-FLS. The ability of survival, migration, and the production of inflammatory factor influenced by exosomal Dvl3 were detected by CKK8 kits, Tunel, migration test, qPCR, and enzyme-linked immunosorbent assay (ELISA) respectively; Flow cytometry analysis was conducted to explorer the inflammatory moderate role of exosomes on CD4+ T cells. The possible downstream pathways of Dvl3 were screened by qPCR and WB and verified by double luciferase reporter experiment. Results The expression level of Dvl3 was significantly increased in RA and CIA. Exosomes from the OE group could significantly promote cell proliferation activity, migration/invasion ability. The augment of TNF-α, IL-1β, IL-17, and IL-21 was observed in exosomal Dvl3-OE group. Th1 and Th17 cells polarisation and cytokines related were both enhanced by Exosomal Dvl3. Over expression of Dvl3 was accompanied by the significant increase of β-catenin and RhoA activities. Conclusion This study discovered the high expression of Dvl3 of exosomes derived from RA patients which may possessed the ability to promote phenotypic transformation of RA-FLS through Wnt pathway.